Village Renewal as an Opportunity for Development of Peripheral Rural Areas of the Pomeranian Region - Czapiewska, Gabriela (Regional Barometer. Analyses & Prognoses, 2011)
Possibility of taking advantage of European funds has influenced for changes in many sectors of agriculture and rural areas. One of most important qualitative change on Polish villages is change of their spatial physiognomy. Rural renewal is the method of development of rural areas. This method is supported by European Union aid programs. The sustainable development of rural areas is not possible without direct and wide participation the occupants of villages. The article presents how the Pomerania region used European Union aid programs for rural renewal and how communes were activated to invest. It focused mostly on the examples of rural renewal realization of the project called “Village renewal and the preservation and protection of the cultural heritage”. Currently, the rural renewal program is its continuation called “Renewal and Development of Rural Areas” (Rural Development Operational Program 2007–1013). It the special attention was paid to activities about social infrastructure implemented in peripheral rural areas of the Pomeranian Voivodship in the frame of Pomeranian Village Renewal Programme.